Correction: HPLC-PDA-MS/MS characterization of bioactive secondary metabolites from Turraea fischeri bark extract and its antioxidant and hepatoprotective activities in vivo - Sobeh, Mansour; Mahmoud, Mona Fouad; Sabry, Omar; Adel, Rasha; Dmirieh, Malak; El Sahzly, Assem; Wink, Michael (Molecules, 2024)
Turraea fischeri is an East African traditional herb, which is widely used in traditional medicine. In this study, we profiled the secondary metabolites in the methanol extract of T. fischeri bark using HPLC-PDA-ESI-MS/MS, and 20 compounds were tentatively identified. Several isomers of the flavonolignan cinchonain-I and bis-dihydroxyphenylpropanoid-substituted catechin hexosides dominated the extract. Robust in vitro and in vivo antioxidant properties were observed in 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay (DPPH) and ferric reducing antioxidant power (FRAP) assay, and in the model organism Caenorhabditis elegans. Additionally, the extract exhibited promising hepatoprotective activities in D-galactosamine (D-GaIN) treated rats. A significant reduction in the elevated levels of aspartate aminotransferase (AST), total bilirubin, gamma-glutamyltransferase (GGT), and malondialdehyde (MDA) and increase of glutathione (GSH) was observed in rats treated with the bark extract in addition to D-galactosamine when compared with rats treated with D-galactosamine alone. In conclusion, T. fischeri is apromising candidate for health-promoting and for pharmaceutical applications.